THE IMPACT OF AUTHENTIC LEADERSHIP ON PROACTIVE WORK BEHAVIOR-AN ANALYTICAL SURVEY STUDY IN SOME HOSPITALS IN THE MIDDLE EUPHRATES REGION - Abbas Khaled Mohan; Hala Hussein Jabr; Ahmed Hassan Shamkhi (Scholar Express Journals, 2025)
This research aims to demonstrate the impact of authentic leadership represented in its dimensions (self-awareness, internal ethical perspective, balanced information processing, and transparency of relationships) and its reflection on proactive work behavior represented in its dimensions (prevention of problems, employee voice, assuming responsibility, and individual creativity) for a sample of medical and nursing staff in some hospitals in the Middle Euphrates region. The size of the researched sample was (334) observations and the total research community was (2400). The researcher sought to achieve a set of goals, including defining authentic leadership and proactive work behavior as important and effective variables in enhancing performance, building a cognitive framework related to these variables and linking them in the field within a descriptive analytical research framework, and then enhancing the future vision of the research variables and directing them in a manner that supports the mission of the organization being researched. The questionnaire was the main tool for collecting data, and a number of statistical methods were used, such as confirmatory structural validity analysis and Pearson's correlation coefficient to measure the type and degree of the relationship between the research variables and structural stability analysis of measurement performance. Cronbach's alpha and the test of the effect between variables (structural equation modeling SEM). The research reached a set of results, the most important of which is the existence of a correlation and positive effect of the influence of authentic leadership on proactive work behavior. The research came out with a set of necessary recommendations to improve the performance of the organizations studied with regard to the research variables
Keywords: Authentic Leadership; Proactive Work Behavior